MicroRNA regulation of viral replication in teleost fish: a review - Chi Zhang; Jiagang Tu; Yong‐An Zhang (Reviews in Aquaculture, 2021)
MicroRNAs (miRNAs) are single‐stranded non‐coding RNA molecules. In addition to participating in various biological processes of eukaryotes, such as cell proliferation, development, differentiation, metabolism, tumorigenesis, and apoptosis, miRNAs also play an important role in the regulation of virus replication. Here, we review the current knowledge on high‐throughput miRNA sequencing of teleost fish or fish cells in response to virus infection, the role of teleost fish miRNAs in regulating virus replication via targeting either fish or virus genes and the function of teleost fish virus‐encoded miRNAs during virus infection. Understanding the interaction between the miRNAs and the host or virus genes will lead to the identification of novel strategy to prevent virus infection in teleost fish.